Breast cancer risk by extent and type of atypical hyperplasia: An update from the Nurses' Health Studies. Issue 4 (13th November 2015) - Collins, Laura C.; Aroner, Sarah A.; Connolly, James L.; Colditz, Graham A.; Schnitt, Stuart J.; Tamimi, Rulla M.
Abstract : BACKGROUND: Women with atypical hyperplasia (AH) on a benign breast biopsy specimen are at increased risk for the development of breast cancer. However, the relation between the type and extent of AH (atypical ductal hyperplasia [ADH] vs atypical lobular hyperplasia [ALH]) and the magnitude of the breast cancer risk is not well defined. METHODS: A nested case‐control study of benign breast disease and breast cancer risk was conducted. Women with breast cancer and prior benign breast biopsy findings (488 cases) were matched to women with prior benign breast biopsy findings who were free from breast cancer (1907 controls). Benign breast biopsy slides were reviewed and categorized as nonproliferative, proliferative without atypia, or AH (ADH or ALH). The number of foci of AH was also recorded. RESULTS: Among women with ADH, the interrelation between the extent of atypia and breast cancer risk was not significant (odds ratio [OR] for 1 or 2 foci, 3.5; 95% confidence interval [CI], 2.2‐5.6; OR for ≥3 foci, 2.7; 95% CI, 1.4‐5.1; P = .41). Similarly, although the risk with ALH was higher for those with ≥3 foci than for those with <3 foci, the difference was not statistically significant (OR for 1 or 2 foci, 5.2; 95% CI, 2.7‐10.0; OR for ≥3 foci, 8.0; 95% CI, 4.5‐14.2; P = .19). CONCLUSIONS: This analysis demonstrates that the extent of ADH or ALH does not significantly contribute to breast cancer risk. The lack of a significant dose‐response relation between the extent and type of atypia and breast cancer risk suggests that it would be premature to use the extent of atypia to influence management decisions for women with ADH or ALH. Cancer 2016;122:515–520. © 2015 American Cancer Society . Abstract : In a case‐control study of benign breast disease and breast cancer risk nested within the Nurses' Health Studies, there is no significant interrelation between the extent of atypical ductal hyperplasia or atypical lobular hyperplasia and breast cancer risk.